Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Strip Story terhadap Kemampuan Menulis Teks Biografi Siswa Kelas X SMA Negeri 8 Medan - Waruwu, Vivin Juliandra; Hanum, Inayah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
Research objectives describe the effect of the problem based learning model assisted by strip story media on the X-grade students of SMA Negeri 8 Medan. Using an experimental method with a two-group post-test-only design The research instruments include biography text and language rules. Data collection techniques included observation, interviews, and tests. The data analysis technique uses the analysis requirement test, normality test, homogeneity test, and hypothesis test. The research results of the post-test class of the control class obtained an average score of 64.71, which is included in the good enough category. The experimental class post-test research results obtained an average value of 82.43, including the good category. The problem based learning learning model assisted by strip story media has a significant effect on the ability to write biography text in class X SMA Negeri 8 Medan, as evidenced by the results of the hypothesis test, which obtained tcount> ttable, namely 9.79 > 1.69, then H0 is rejected and Ha is accepted.